(untitled) (Theatrum historiae, 2017)
The present study focuses on documenting the beginnings of the diplomatic career of one of the most important imperial diplomats, Dominik Andreas Count von Kaunitz (1655–1705) and on defining the information that was learned within the context of the current research. Researchers have already studied the peak period of Kaunitz’ diplomatic career in the late 1690’s, when he served in the Hague as the imperial envoy and was subsequently appointed as the Reichsvizekanzler. His previous activities, however, have so far not aroused much interest, though it was the 80’s and the beginning of the 90’s of the 17th century that were crucial in regard to his future direction. Based on the research that was carried-out in the Moravský zemský archiv in Brno (Moravian Land Archive, in the Kaunitz and Dietrichstein Family Archives) and in the archives in Vienna (in Haus-, Hof- und Staatsarchiv and Allgemeines Verwaltungsarchiv) and also in the Munich archive (Bayerisches Hauptstaatsarchiv) attention will be paid not only to what, when and where Count von Kaunitz discussed during his journeys, but also the manner in which he acted and the strategies that he chose to employ. This study should therefore reveal not only this diplomat’s mental world but also his everyday life and his social background.